Integration of Renewable Energy Sources Into the Energy System - Mammadli, Mammad (ADA University, 2024)
This thesis discusses the integration of renewable energy sources into electrical power systems, with a focus on the design, simulation, and optimization of a 445 MW solar power plant located in Bilasuvar, Azerbaijan. Using highly specialized software like PVsyst and PowerFactory, the study evaluates the prospect of energy production, grid stability, environmental benefits, and economic feasibility. Establishing the solar park will not only lower greenhouse gas emissions, in line with Azerbaijan's sustainability objectives and the global push to adapt clean and efficient systems, but also satisfy the rising energy demands of Azerbaijan at the same time. Analysis results presented a high level of system efficiency and operational reliability, providing evidence of its annual yield of 684 GWh and an 87.7% Performance Ratio. The study analyzes the power system's stability at different states of solar irradiance, demonstrating the efficient integration of solar power in Azerbaijan's electrical grid. Simulation results under PowerFactory underline the importance of dynamic stability in terms of guaranteeing a non-interrupted supply of energy even under changes in solar production. Furthermore, the environmental assessment presents a huge impact: more than 3 gigatons of CO₂ emissions avoided over the whole 30-year lifetime of the plant, underscoring the importance of this project for fighting climate change. The financial analyses confirm economic viability through a payback period of 10.9 years and an investment return of 129.6%, hence very attractive to stakeholders and investors. The Bilasuvar Solar Park epitomizes Azerbaijan's potential in harnessing solar energy using its geographical advantages of high solar irradiance and favorable climatic conditions. This is further enabled by the incorporation of advanced technologies like monocrystalline photovoltaic modules and central inverters with Maximum Power Point Tracking (MPPT) to improve energy yield and system reliability. The thesis provides pragmatic recommendations for improving the efficiency of a solar plant, dealing with losses in the system, and optimizing design parameters in large-scale solar projects. This will improve the integration of renewable energy in existing power grid infrastructures as a whole through advanced simulation. It puts forward flexible solutions applicable in various contexts and underlines innovative methodologies needed for the deployment of renewable energies. This, in fact, gives the greatest importance to proper planning and highly complex simulation methods involving collaboration between energy planners, policymakers, and industry actors. The results from this research are supposed to lead future initiatives on renewable energy, helping Azerbaijan transform towards a sustainable energy future and providing a framework for addressing global energy and environmental challenges.
Keywords: Azerbaijan -- Energy policy -- Renewable energy; Solar power -- Azerbaijan -- Design and construction; Renewable energy -- Integration -- Azerbaijan; Energy optimization -- Solar power systems; IT and Engineering